The development of sisperman games on science teaching for primary school student - Juliana Juliana; Nurul Kemala Dewi; Baiq Niswatul Khair (Jurnal Pijar Mipa, 2021)
This study aims to determine the development steps and the feasibility of the Sisperman snake and ladder game media in science learning for the fifth-grade students of Elementary School Students, SDN 1 Labuan Lombok, in the 2020/2021 school year. The ADDIE model (analysis. design, development, implementation, evaluation) developed by Robert Maribe Brach was applied for producing the learning media. The study subjects were 24 students of fifth-grade students. The data collection was done by interviewing, observing, documenting, and filling out questionnaires. Qualitative and quantitative data analysis techniques were implemented for analysis techniques. This study indicates that the developed Sisperman snake and ladder game media is very suitable for being used as a learning medium. The final assessment obtained from the media expert test getting a percentage value of 96.42%. It means the media is categorized as highly valid criteria. From material content, the experts give the score a percentage value of 91.66%, which shows highly good criteria. The practicality from the student responses offers a percentage value of 92.01% with highly practice criteria.